Peran Motivasi Belajar Terhadap Aktivitas Belajar Siswa di MTs Al Urwatul Wutsqo Jombang - Gatot Marwoko Chahya Ansyani; pengelola, pengelola (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2021)
This research is motivated by the researcher's curiosity about the role of learning motivation on student learning activities at MTs Al-Urwatul Wutsqo Jombang. This type of research is field research using a qualitative descriptive approach. The data collection methods used are interview, observation, and documentation methods. While the analysis method used is inductive. The results showed that showed that learning motivation contributes to student learning activities, students have a strong drive to carry out more quality learning activities.